GENETICALLY MODIFIED AGRIFOOD TRADE: NECESSITY OR CONCERNS? - Nurliza, Nurliza (Jurnal Social Economic of Agriculture, 2013)
Genetically modified agri-foods are genetically modified using biotechnology. Genetically modified organisms (GMOs) advantages are the focus of much attention in world food markets. Genetically modified crop technology is claimed also to have great potential for the worlds farmers and ultimately consumers, following initial success with genetically modified cotton varieties. Benefits for farmers could include greater productivity and less occupational health and environmental damage (e.g., fewer pesticides), while benefits to consumers include lower food prices and, potentially, enhanced attributes. Common genetically modified agri-foods include maize, soybeans, oilseed rape (canola), chicory, squash, potatoes, pineapples and strawberries. Genetically modified agri-foods are designed for greater resistance to pests and viruses, higher nutritional value and longer shelf life. However, their safety, potential risks and ethical concerns are still being debated. Laws to regulate labeling of genetically modified agri-foods vary. The public's perception of the risk of new technology is critical to its acceptance. Perception of risk, in turn, depends on the credibility of the source of the information and trust in the regulatory process. Keyword: Genetically modified agri-food, trade, concerns, necessity